2016
DOI: 10.1097/mca.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in left ventricular function after a percutaneous coronary intervention

Abstract: Changes in LVEF after elective PCI occur often. Both higher baseline LVEF and post-PCI LVEF normalization are associated with improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Participants in 6 studies [ 13 , 14 , 30 , 31 , 32 , 33 ] were exclusively patients with STEMI, in 3 studies [ 34 , 35 , 36 ] participants were exclusively patients with CTO, and 3 studies [ 31 , 37 , 38 ] were patients with baseline heart failure. Thirteen studies [ 11 , 30 , 31 , 32 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] reported the prognostic outcomes during hospitalization, 14 studies [ 14 , 33 , 34 , 35 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] reported the prognostic outcomes for greater than or equal to one year, and 6 studies [ 10 , 13 , 36 , 56 , 57 , 58 ] reported the prognostic outcomes in both short and long term. The characteristics of the included studies are detailed (Table 1 , Ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants in 6 studies [ 13 , 14 , 30 , 31 , 32 , 33 ] were exclusively patients with STEMI, in 3 studies [ 34 , 35 , 36 ] participants were exclusively patients with CTO, and 3 studies [ 31 , 37 , 38 ] were patients with baseline heart failure. Thirteen studies [ 11 , 30 , 31 , 32 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] reported the prognostic outcomes during hospitalization, 14 studies [ 14 , 33 , 34 , 35 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] reported the prognostic outcomes for greater than or equal to one year, and 6 studies [ 10 , 13 , 36 , 56 , 57 , 58 ] reported the prognostic outcomes in both short and long term. The characteristics of the included studies are detailed (Table 1 , Ref.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are detailed (Table 1 , Ref. [ 10 , 11 , 13 , 14 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]). The average NOS score of all included studies was 7.6 points, with 2 studies having a minimum score of 5 [ 32 , 34 ] and 3 studies having score of 6 [ 30 , 40 , 43 ] ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In analysis of hospitalization rates for HF, PPM and VVI‐mode pacing are strong hazardous predictors of HF hospitalization. Previous researches have showed that multiple factors, such as T2DM, LVEF, and renal insufficiency, were risk in the prognosis of patients following PCI. After adjustment for risk factors, we discovered that PPM was still an independent predictor of the rate of HF‐related hospitalization, whereas VVI‐mode pacing no longer was, which may be caused by our small sample capacity.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is important to distinguish between CAD-and non-CAD-related HFrEF in the initial assessment of patients presenting with new-onset HFrEF of unknown etiology, since CAD-related HFrEF usually requires revascularization in order to improve symptoms and longterm prognosis. 2,3 As such, it has been common practice to exclude CAD by invasive coronary angiography (ICA) independently of risk factors or medical history as a first-line approach. However, there are data showing that patients with left ventricular systolic dysfunction without chest pain or previous MI are unlikely to present extensive coronary disease that could explain left ventricular dysfunction or to have coronary anatomy suitable for bypass grafting.…”
Section: Introductionmentioning
confidence: 99%